Frontiers and Best Practices in Bio, Circular, and Green Growth and Eco-Innovation (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
After almost two decades of continuous development in bio, circular, and green economy, the time is ripe for the assessment of the major achievements and challenges that private and public enterprises face today to further enhance these global sustainability concepts. Due to the central role of political incentives for the development and implementation of environmentally friendly and sustainable practices, the present book project focuses on the nexus between public policies, institutions, quality of public sector management, and patterns of interaction between government and private businesses in backing bio, green, and circular economy practices and eco-innovation. In addition, the project also accommodates surveys that elaborate on the differences between the implementation of new organizational forms and scientific innovations in technologically advanced and developing settings.